Nitric oxide signaling and cysteine protease activity in the modulation of abiotic stress responses in soybean and maize - Bilibana, Mawethu Pascoe (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MSc (Plant Biotechnology))--University of Stellenbosch, 2010.